2022
DOI: 10.3390/ma15196633
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Surface Texture of Thermoplastic (Monomer-Free) Dental Materials Due to Some Minor Alterations in the Laboratory Protocol—Preliminary Study

Abstract: Contemporary thermoplastic monomer-free prosthetic materials are widely used nowadays, and there are a great variety available on the market. These materials are of interest in terms of the improvement of the quality features of the removable dentures. The aim of this study is to establish how minimal changes in the laboratory protocol of polyamide prosthetic base materials influence the surface texture. Two polyamide materials intended for the fabrication of removable dentures bases were used—Perflex Biosens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In order to remedy this, minimal changes in the injection manufacturing protocol of two PA prosthetic base materials were tested in vitro (Perflex Biosens (BS), Netanya, Israel and VertexTM ThermoSens (TS), Soesterberg, The Netherlands. By slightly modifying the melting temperature (5 °C) and pressure (0.5 bar), no improvement in the surface finish was observed for Biosens, whereas for ThermoSens, the surface roughness was significantly reduced Chuchulska, 2022 [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to remedy this, minimal changes in the injection manufacturing protocol of two PA prosthetic base materials were tested in vitro (Perflex Biosens (BS), Netanya, Israel and VertexTM ThermoSens (TS), Soesterberg, The Netherlands. By slightly modifying the melting temperature (5 °C) and pressure (0.5 bar), no improvement in the surface finish was observed for Biosens, whereas for ThermoSens, the surface roughness was significantly reduced Chuchulska, 2022 [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thermoplastic materials utilized in dentistry encompass composite substances or copolymers with thermoplastic attributes. These materials offer benefits such as monomer-free composition, absence of toxic or allergenic additives, high biocompatibility, shape retention, plasticity, precision in fabrication, color diversity, and expanded applications in various prosthetic scenarios, including partial and total prosthetics, immediate and post-resection prosthetics, prosthetics postimplantation, and aesthetic enhancement of prostheses [30]. As of present, the following categories of thermoplastic materials have been identified and utilized in the fabrication of removable dental prostheses due to their elastic and flexible properties:…”
Section: Recent Assessment Of the Mechanical Properties Of Convention...mentioning
confidence: 99%
“…While Sharabasy et al determined bacterial adhesion to the surfaces of injection plastics to be unlikely [29], reports of subdenture stomatitis in patients utilizing polyamide prosthetic materials indicate engagement on both prosthetic surfaces and mucous membranes [45]. Polyamide injection materials exhibited maximum bacterial adhesion and colony formation, surpassing even conventional PMMAs [30]. Despite their susceptibility to surface defects and high roughness levels, these materials are challenging to polish, fostering pathogen colonization [34].…”
Section: Biocompatibility Of Traditional Polymers Applied In Prosthod...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, favorable changes were also recorded; hardness and flexural modulus increased whereas volume loss during the wear test decreased with the introduction of ceramic particles [ 16 ]. Chuchulska et al [ 17 ], in the technological study, tested how the small changes in the laboratory protocol of polyamide prosthetic base materials may influence the surface texture. Investigations have shown that modifying the process by altering the melting temperature by 5 °C and the pressure by 0.5 Bar during injection molding can reduce roughness for some materials.…”
mentioning
confidence: 99%